Analisis Keadilan Organisasi dalam Mewujudkan Lingkungan Inklusif di KSP Faomasi Baluse Mandiri - Fau, Karolina; Rahayu, Enik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the implementation of organizational justice in KSP FAOMASI BALUSE MANDIRI, with a focus on distributive, procedural, and interactional justice in cooperatives. The problem focuses on the transparency of profit distribution, member participation in decision-making, and the quality of communication between cooperative management and members. In order to approach this problem, this study uses the theory of organizational justice as the main reference. Data were collected through observation, in-depth interviews with cooperative members and management, and analysis of related documents, then analyzed qualitatively to identify patterns and challenges faced by cooperatives in implementing the principle of organizational justice. This study concludes that although cooperatives have attempted to implement the principle of organizational justice, there are still challenges in the aspects of information transparency, member participation in decision-making, and communication between management and members. Some members feel that they do not have access to clear information regarding profit distribution, as well as the lack of opportunities to convey aspirations in the annual deliberation forum. Therefore, it is necessary to improve more inclusive communication mechanisms, strengthen the complaint system, and utilize digital technology to support transparency and more active member involvement. With improvements in these aspects, cooperatives can create a fairer, more transparent, and participatory management system, so as to increase member satisfaction and loyalty in a sustainable manner